Natriuretic Hormone: The Ultimate Determinant of the Preservation of External Sodium Balance - Bricker, Neal S.; Cain, Christopher D.; Shankel, Stewart (Frontiers in Endocrinology, 2014)
The present manuscript focuses on a putative natriuretic hormone. It includes the history of a long-term search for the pure molecule, ranging from partial purification to synthesis. It includes a description of seven different bioassay systems used, a resume of the sequential steps in purification, and a summary of a series of experimental protocols employed in the effort to define the biologic properties of the inhibitor of Na transport. Two closely related molecules were purified and synthesized. Both are xanthurenic acid derivatives (xanthurenic acid 8-O-beta-D-glucoside and xanthurenic acid 8-O-sulfate). It is concluded that one or both of these two low molecular weight compounds (MW: 368 and 284) meet many of the criteria for the final modulator of Na excretion